Shaping Career Satisfaction: The Influence of Professional Training and Expectations in Winter Hotel Employees - Ahmet Çavuş; Furkan Zirzakıran; Leyla Tokgöz (SAGE Open)
This study aims to examine the impact of professional progress, industry change challenges, and professional achievement on career satisfaction among winter hotel employees. By focusing on these key constructs, the research seeks to understand how specialized training and individual career expectations influence employees’ satisfaction levels. Additionally, the study investigates the moderating roles of career expectations and tourism education in the relationship between industry change challenges and career satisfaction. By examining how these factors interact, the research aims to provide a nuanced understanding of the dynamics that enhance employee satisfaction and retention in the winter tourism sector. The insights derived from this research are expected to offer valuable guidance for stakeholders in developing strategies that support both career development and educational enrichment, thereby promoting a more satisfied and committed workforce. The study targeted 157 out of 238 employees at the Palandöken Winter Tourism Center, employing a comprehensive survey methodology. Exploratory factor analysis was conducted to establish the sub-scales of the research. Following this, Hierarchical Multiple Regression Analysis was used to test the research questions. Results indicated that professional progress and professional achievement significantly positively impact career satisfaction. The study also revealed that career expectations and tourism education moderated the relationship between industry change challenges and career satisfaction, emphasizing the role of tailored educational programs. Despite this, industry change challenges had a lesser impact on career satisfaction compared to other factors, yet they still played a role in shaping overall employee contentment. Interestingly, no significant differences were found in career expectations based on employees’ gender, business divisions, or work shifts. These findings offer novel insights into employee satisfaction within the winter tourism sector, particularly in the context of winter hotel tourism in Turkey.